Effects of replacing fish meal with pork meal and supplementing with crystalline amino acids and fish oil on growth performance, body composition, enzyme activity, intestinal morphology, and immune response of Penaeus monodon - Chen, Qiuchi; Zhang, Chunxiao; Yun, Biao; Wang, Sheng; Ma, Jun; Qian, Xueqiao (Frontiers in Marine Science, 2024)
Introduction The present study aimed to evaluate the effects of substituting fish meal with pork meal in feed on the growth performance, feed utilization, intestinal morphology, and immune function of Penaeus monodon. Methods A total of 600 uniformly sized juvenile shrimp with an initial weight of 1.20 ± 0.03 g were randomly assigned to four groups, with each group consisting of six replicates of 25 shrimp each. Fish meal protein was replaced with 0%, 5%, 10%, and 15% pork meal, and crystalline amino acids and fish oil were supplemented accordingly. The groups were designated as P0, P5, P10, and P15, and the study duration was 70 days. Results Results indicated no significant difference in specific growth rate (SGR) between the P5 and P10 groups compared to the P0 group. However, the SGR in the P15 group was significantly lower than that in the P5 and P10 groups. Feed conversion rates (FCRs) for the P5 and P10 groups were comparable to the P0 group, whereas the P15 group showed a significantly higher FCR than the other groups. There were no significant differences in whole body composition among all the groups. Apart from alanine, the amino acid composition of muscles did not differ significantly among all the groups. Results of enzyme activity in plasma revealed that the replacement of fish meal with pork meal reduced levels of aspartate aminotransferase (AST) and superoxide dismutase (SOD). Specifically, levels of AST in the P5 and P15 groups were significantly lower compared to the P0 and P10 groups. Histological examination of midgut tissues showed that villus height initially increased and then decreased with higher replacement ratios. The P5 group had the highest villus height, while the P15 group had the lowest villus height. Analysis of gene expression related to liver immune functions indicated that genes in TLR signaling pathway were significantly elevated in the P15 group compared to the other groups. Discussion In conclusion, even with the supplementation of crystalline amino acids and fish oil, pork meal should not replace more than 10% of fish meal in the feed of P. monodon to maintain optimal growth and feed efficiency.